A polyvinyl acetate emulsion woodworking adhesive with long open time and strong moisture resistance
By designing a glue structure with core layer and shell layer in polyvinyl acetate emulsion adhesive, the problems of short opening time and poor moisture resistance of existing adhesives are solved, and long opening time and high moisture resistance are achieved, satisfying the satisfaction of The demand for wood products production.
Patent Information
- Application Number
- CN202410542377.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The existing polyvinyl acetate emulsion adhesives have a short opening time and poor moisture resistance, which cannot meet the demand for long opening time and high humidity resistance in wood products production.
By introducing a structure with a core layer and a shell layer into the colloid, the core layer consists of vinyl acetate and polysaccharides with a molecular weight of 1000 to 5000, and the shell layer consists of vinyl acetate and vinyl tertiary carbonate to form a crosslinking network to improve water retention and prevent moisture volatility through hydrophobic shells.
It realizes the long opening time and high moisture resistance of polyvinyl acetate emulsion adhesive, meeting the demand for improving bond strength in wood product production.
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, and in particular to a polyvinyl acetate emulsion woodworking adhesive with a long open time and strong moisture resistance. Background Art
[0002] PVAc, polyvinyl acetate emulsion adhesive, commonly known as white latex, is mainly used in wood, prevention, coating and other industries. It is a milky white viscous liquid prepared by polymerization of vinyl acetate monomer under the action of initiators, protective adhesives and other materials. It is one of the water-based adhesives with the highest production in China. Polyvinyl acetate emulsion adhesives have strong stability and good adhesion, but their moisture resistance and cold resistance are poor. Polyvinyl acetate emulsion adhesives are cured by the volatilization of water, and the rate of water volatilization affects its open time.
[0003] my country is a major producer and consumer of wood products, and wood adhesive is a widely used bonding material in the production process of wood products. In the bonding process of wood products, due to the needs of the process, multiple wood products will be glued and then further pressed. The open time of conventional polyvinyl acetate emulsion adhesives is short, and the glue layer of the wood products has been solidified before pressing, so that the ideal bonding strength cannot be achieved. Therefore, it is a problem that those skilled in the art are urgently trying to solve to modify polyvinyl acetate emulsion adhesives to improve their open time. CN109355039A discloses a long open time woodworking adhesive based on maltose syrup modified polyvinyl acetate emulsion, which forms a cross-linked network with hydrophilic and hydrophobic groups with polyvinyl acetate by introducing maltose syrup rich in hydroxyl groups and seaweed powder rich in ether. There is an internal hydrophilic network in some networks, which plays the role of a container for accommodating water molecules, thereby improving water retention and extending the open time. Introducing hydroxyl groups and ether groups into polyvinyl acetate emulsion can enhance its water retention performance, but at the same time these groups will also easily combine with moisture, resulting in reduced viscosity of the adhesive, further reducing the moisture resistance of polyvinyl acetate emulsion adhesives. Other researchers have also used other modification methods to enhance the water retention of polyvinyl acetate emulsions, such as adding water-retaining agents, but they will inevitably lead to further reductions in the moisture resistance of polyvinyl acetate emulsions.
[0004] Therefore, it is necessary to provide a polyvinyl acetate emulsion woodworking adhesive with a long open time and strong moisture resistance. Summary of the invention
[0005] The first aspect of the present invention provides a polyvinyl acetate emulsion woodworking adhesive with a long open time and strong moisture resistance, comprising colloid particles and a dispersant, wherein the colloid particles comprise a core layer and a shell layer, the preparation material of the core layer comprises vinyl acetate and a polysaccharide with a molecular weight of 1000 to 5000, and the preparation material of the shell layer comprises vinyl acetate and versatate.
[0006] The adhesive of the present invention comprises colloid particles having a core layer and a shell layer, and a polysaccharide with a molecular weight of 1000 to 5000 is introduced into the preparation material of the core layer, and the polysaccharide of the molecular weight has abundant hydroxyl groups, a part of which can be combined with the ester group, hydroxyl group, and carboxyl group on the polymer chain of polyvinyl acetate to form a cross-linked network, and a part of which can be combined with water molecules as a hydrophilic group to bind the water molecules in the cross-linked network, thereby improving the water retention capacity of the core layer; the preparation raw material of the shell layer comprises tert-butyl vinyl carbonate, and the tert-butyl vinyl carbonate monomer is highly hydrophobic, so the shell layer formed has stronger hydrophobicity, which can improve the moisture resistance of the shell layer on the one hand, and prevent the volatilization of water inside the core layer on the other hand, further improving the open time of the adhesive. Therefore, the adhesive of this scheme not only has a longer open time, but also has stronger moisture resistance.
[0007] Furthermore, the weight ratio of the vinyl acetate to the versatate is (3-5): 1. If the content of versatate is too high, the adhesion effect of the adhesive will be affected; if the content of versatate is too low, the hydrophobicity of the shell layer will not meet the requirements, affecting moisture resistance and open time.
[0008] Furthermore, the polysaccharide includes cyclodextrin, which is a cyclic oligosaccharide containing a hydrophobic cavity and a hydrophilic outer layer, and can be bound to a polymer chain through inclusion complexation, and has more active hydroxyl groups, which can greatly increase the hydrophilicity of the polymer chain.
[0009] Furthermore, in terms of weight, in the raw materials for preparing the core layer, the ratio of the vinyl acetate to the polysaccharide is 25:(0.5-1). If the ratio of polysaccharides is too low, the water retention of the core layer will be reduced, thereby shortening the open time of the adhesive; if the ratio of polysaccharides is too high, there will still be a lot of free polysaccharides after the polymerization of the seed colloid, and the free polysaccharides will participate in the subsequent polymerization step of the shell layer, thereby reducing the hydrophobicity of the shell layer. Furthermore, in terms of weight, in the raw materials for preparing the core layer, the ratio of the vinyl acetate to the polysaccharide is 25:(0.5-0.7). Adhesives using the above ratio have a longer open time.
[0010] Furthermore, the ratio of vinyl acetate in the raw materials for preparing the core layer to the raw materials for preparing the shell layer is 1:(4-7) by weight. By controlling the ratio of vinyl acetate in the raw materials for preparing the core layer and the shell layer, the thickness ratio of the core layer and the shell layer of the particle is adjusted, so that the core layer can play a role in retaining moisture, and the shell layer can prevent the volatilization of moisture in the core layer.
[0011] Furthermore, the raw materials for preparing the shell layer also include a hydrophilic initiator. The present invention uses a hydrophilic core layer and a hydrophobic shell layer. If a hydrophilic initiator is used, a strawberry-shaped structure or a core-shell structure can be formed, and the hydrophobic shell layer can better cover the hydrophilic core layer. Furthermore, the hydrophilic initiator is ammonium persulfate.
[0012] Furthermore, the raw materials for preparing the core layer include protective colloid.
[0013] A second aspect of the present invention provides a method for preparing a polyvinyl acetate emulsion woodworking adhesive, comprising the following steps:
[0014] 30-40 parts by weight of the vinyl acetate monomer and 8-12 parts by weight of the versatate vinyl carbonate monomer are mixed to prepare a mixed monomer; 60-80 parts by weight of deionized water, 0.2-0.4 parts by weight of an emulsifier, and 0.1-0.5 parts by weight of a pH buffer are added to a reaction kettle, 2-3 parts by weight of the protective colloid and 0.2-0.4 parts by weight of the polysaccharide are added under dispersing and stirring conditions, the temperature is raised to 80-85° C. after dispersion, and the temperature is lowered to 40-60° C. after complete dissolution, and 6-1 0 parts by weight of the vinyl acetate monomer and 1-2 parts by weight of the initiator solution, heating to 70-80° C. for 20-40 minutes of polymerization reaction to obtain a seed emulsion; the mixed monomer and 3-5 parts by weight of the initiator solution are respectively and simultaneously added dropwise to the seed emulsion for 3-4 hours, and after the addition is completed, the temperature is raised to 70-80° C., the polymerization reaction is carried out for 50-80 minutes, and then cooled to 30-40° C., and the material is filtered to obtain the polyvinyl acetate emulsion woodworking adhesive. DETAILED DESCRIPTION
[0015] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0016] Example 1
[0017] 40 kg of vinyl acetate monomer and 13 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer;
[0018] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into a reactor and mix. Add 2.5kg of polyvinyl alcohol and 0.2kg of β-cyclodextrin under dispersed stirring conditions. After stirring and dispersing, heat to 85°C until completely dissolved, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C for polymerization reaction, and the time is 30min to obtain a seed emulsion.
[0019] 53 kg of mixed monomers and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added simultaneously (two reagents were added simultaneously through two pipelines, and the addition was completed at the same time) into the reactor of the seed emulsion for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes, then cooled to 35°C, and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0020] Example 2
[0021] 30 kg of vinyl acetate monomer and 8 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer.
[0022] Add 60kg of deionized water, 0.25kg of emulsifier PCA507, and 0.3kg of pH buffer sodium bicarbonate into a reactor and mix. Add 3kg of polyvinyl alcohol and 0.16kg of β-cyclodextrin under dispersed stirring conditions. After stirring and dispersing, heat to 85°C to dissolve completely, then cool to 50°C, add 8kg of vinyl acetate monomer and 1kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C for polymerization reaction, and the time is 40min to obtain a seed emulsion.
[0023] 38 kg of mixed monomers and 3 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 4 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 70 minutes. Then the mixture was cooled to 40°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0024] Example 3
[0025] 40 kg of vinyl acetate monomer and 4 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer.
[0026] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into a reactor and mix. Add 2.5kg of polyvinyl alcohol and 0.2kg of β-cyclodextrin under dispersed stirring conditions. After stirring and dispersing, heat to 85°C until completely dissolved, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C for polymerization reaction, and the time is 30min to obtain a seed emulsion.
[0027] 44 kg of mixed monomers and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the mixture was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0028] Example 4
[0029] 40 kg of vinyl acetate monomer and 13 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer.
[0030] 75 kg of deionized water, 0.3 kg of emulsifier PCA507, and 0.2 kg of pH buffer sodium bicarbonate were added to a reactor for mixing. Under dispersed stirring conditions, 2.5 kg of polyvinyl alcohol and 0.2 kg of maltose syrup (the main components are isomaltose (IG2), panose (P), isomaltotriose (IG3) and oligosaccharides of tetrasaccharides (including tetrasaccharides) or above (Gn)) were added. After stirring and dispersing, the temperature was raised to 85° C. and dissolved completely, then the temperature was lowered to 50° C., 10 kg of vinyl acetate monomer and 1.5 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added, the temperature was raised to 80° C. for polymerization reaction, and the time was 30 min to obtain a seed emulsion.
[0031] 53 kg of mixed monomers and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the mixture was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0032] Example 5
[0033] 40 kg of vinyl acetate monomer and 13 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer.
[0034] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into a reactor and mix. Add 2.5kg of polyvinyl alcohol and 0.4kg of β-cyclodextrin under dispersed stirring conditions. After stirring and dispersing, heat to 85°C until completely dissolved, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C for polymerization reaction, and the time is 30min to obtain a seed emulsion.
[0035] 53 kg of mixed monomers and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the mixture was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0036] Comparative Example 1
[0037] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into the reactor and mix. Add 2.5kg of polyvinyl alcohol under dispersion and stirring conditions. After stirring and dispersing, heat to 85°C to dissolve completely, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C to carry out polymerization reaction for 30 minutes to obtain a seed emulsion.
[0038] 40 kg of vinyl acetate monomer and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the temperature was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0039] Comparative Example 2
[0040] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into a reactor and mix. Add 2.5kg of polyvinyl alcohol and 0.2kg of β-cyclodextrin under dispersed stirring conditions. After stirring and dispersing, heat to 85°C until completely dissolved, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C for polymerization reaction, and the time is 30min to obtain a seed emulsion.
[0041] 40 kg of vinyl acetate monomer and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the temperature was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0042] Comparative Example 3
[0043] 40 kg of vinyl acetate monomer and 13 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer.
[0044] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into the reactor and mix. Add 2.5kg of polyvinyl alcohol under dispersion and stirring conditions. After stirring and dispersing, heat to 85°C to dissolve completely, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C to carry out polymerization reaction for 30 minutes to obtain a seed emulsion.
[0045] 53 kg of mixed monomers and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the mixture was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0046] Comparative Example 4
[0047] 40 kg of vinyl acetate monomer and 13 kg of versatate vinyl carbonate monomer were mixed to prepare a mixed monomer.
[0048] Add 75kg of deionized water, 0.3kg of emulsifier PCA507, and 0.2kg of pH buffer sodium bicarbonate into a reactor and mix. Add 2.5kg of polyvinyl alcohol and 1kg of β-cyclodextrin under dispersed stirring conditions. After stirring and dispersing, heat to 85°C until completely dissolved, then cool to 50°C, add 10kg of vinyl acetate monomer and 1.5kg of initiator (2% by mass ammonium persulfate aqueous solution), heat to 80°C for polymerization reaction, and the time is 30min to obtain a seed emulsion.
[0049] 53 kg of mixed monomers and 4 kg of initiator (2% by mass ammonium persulfate aqueous solution) were added dropwise into the reactor of the seed emulsion respectively for 3 hours. After the addition was completed, the temperature was raised to 80°C and kept warm for 60 minutes. Then the mixture was cooled to 35°C and the material was filtered to obtain polyvinyl acetate emulsion woodworking adhesive.
[0050] Test Method
[0051] Open time test: (1) Select a flat MDF board and use a 100g applicator to evenly apply the glue to be tested on the MDF board and start timing.
[0052] (2) Initial test of open time: After 10 minutes, gently place a cotton ball on the surface of the film, and blow gently in the horizontal direction with your mouth 15 cm away from the cotton ball. If it can be blown away without leaving any cotton threads on the surface of the glue, it is surface dry. Otherwise, it cannot be blown away or cotton threads remain. Repeat the cotton ball blowing method every 1 minute until the open time T is measured.
[0053] (3) Accurately test the open time: After measuring the open time, measure the open time again by blowing a cotton ball at (T table - 1) minutes (if the surface is determined to be dry, it is necessary to verify it twice with a cotton ball); and accurately measure the open time again. The average time of the next two accurate measurements is expressed as the open time of the glue.
[0054] Moisture resistance test: 2 birch boards of 2.5cm×2.5cm, clean the surface of the boards, draw a line 0.5cm away from one end of the wood block. Take 0.0500-0.0520g of the finished emulsion, evenly apply it on the flat front board of 2.5cm×2.0cm at the other end, and do not apply the other board. The two boards are overlapped and placed in a fixture with fixed pressure, and placed at room temperature for 24 hours. Then soak the bonded boards in 80℃ water, measure the debonding time, repeat 5 times and take the average value.
[0055] Table 1
[0056] Opening hours Glue opening time / day Example 1 61 minutes 32.3 Example 2 58 minutes 31.4 Example 3 52 minutes 23.7 Example 4 54 minutes 25.1 Example 5 55 minutes 27.4 Comparative Example 1 20 minutes 15.2 Comparative Example 2 33 minutes 16.6 Comparative Example 3 32 minutes 32.1 Comparative Example 4 48 minutes 20.8
[0057] According to the data in Table 1, the open time of Examples 1-5 is better than that of Comparative Examples 1-3. This is because the adhesive of the present invention has a special colloid structure. A polysaccharide with a molecular weight of 1000 to 5000 is introduced into the preparation material of the core layer. The polysaccharide with this molecular weight has abundant hydroxyl groups, a part of which can be combined with the ester group, hydroxyl group, and carboxyl group on the polymer chain of polyvinyl acetate to form a cross-linked network, and a part of which can be combined with water molecules as a hydrophilic group to bind the water molecules in the cross-linked network, thereby improving the water retention capacity of the core layer; the raw materials for the preparation of the shell layer include tert-butyl vinyl carbonate, and the tert-butyl vinyl carbonate monomer is highly hydrophobic, so the shell layer formed has stronger hydrophobicity, which can prevent the volatilization of water inside the core layer, and further improve the open time of the adhesive. The open time of Comparative Examples 2 and 3 is improved compared with Comparative Example 1, but not as good as that of Examples 1-5, which shows that the core layer and the shell layer have a synergistic effect. The moisture resistance of Examples 1-5 is worse than that of Comparative Examples 1-2, because Examples 1-5 use a hydrophobic shell layer. Although Comparative Example 4 also uses a hydrophobic monomer as a shell material, because it uses an excessive amount of polysaccharide, part of the polysaccharide is incorporated into the shell, affecting the hydrophobicity of the shell, thereby shortening its open time and reducing its moisture resistance.
[0058] Compared with Example 1, Example 3 has a shorter open time and weaker moisture resistance, because the hydrophobic monomer used in its shell is too little. Compared with Example 4, Example 1 has a longer open time, because cyclodextrin is a cyclic oligosaccharide containing a hydrophobic cavity and a hydrophilic outer layer, which can be bound to the polymer chain through inclusion complexation, has more active hydroxyl groups, and can greatly improve the hydrophilicity of the polymer chain. Compared with Example 5, Example 1 has a longer open time and better moisture resistance, because the preferred polysaccharide content is used.
[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polyvinyl acetate emulsion woodworking adhesive with long open time and strong moisture resistance, characterized in that: The invention comprises colloid particles and a dispersant, wherein the colloid particles comprise a core layer and a shell layer, wherein the material for preparing the core layer comprises vinyl acetate and a polysaccharide with a molecular weight of 1000 to 5000, and the raw material for preparing the shell layer comprises vinyl acetate and vinyl ester carbonate, wherein the weight ratio of the vinyl acetate to the vinyl ester carbonate in the raw material for preparing the shell layer is (3 to 5):1, and the polysaccharide comprises cyclodextrin, wherein the ratio of the vinyl acetate to the polysaccharide in the raw material for preparing the core layer is 25:(0.5 to 1) in parts by weight, and the ratio of the vinyl acetate in the raw material for preparing the core layer and the raw material for preparing the shell layer is 1:(4 to 7).
2. The polyvinyl acetate emulsion woodworking adhesive according to claim 1, characterized in that: In parts by weight, in the raw materials for preparing the core layer, the ratio of the vinyl acetate to the polysaccharide is 25:(0.5-0.7).
3. The polyvinyl acetate emulsion woodworking adhesive according to claim 1, characterized in that: The raw materials for preparing the shell layer also include a hydrophilic initiator.
4. The polyvinyl acetate emulsion woodworking adhesive according to claim 3, characterized in that: The hydrophilic initiator is ammonium persulfate.
5. The polyvinyl acetate emulsion woodworking adhesive according to claim 1, characterized in that: The raw materials for preparing the core layer include protective colloid.
6. The method for preparing the polyvinyl acetate emulsion woodworking adhesive according to any one of claims 1 to 5, characterized in that: The following steps are involved: 30-40 parts by weight of the vinyl acetate monomer and 8-12 parts by weight of the versatate vinyl carbonate monomer are mixed to prepare a mixed monomer; 60-80 parts by weight of deionized water, 0.2-0.4 parts by weight of an emulsifier, and 0.1-0.5 parts by weight of a pH buffer are added to a reaction kettle, 2-3 parts by weight of the protective colloid and 0.2-0.4 parts by weight of the polysaccharide are added under dispersing and stirring conditions, the temperature is raised to 80-85° C. after dispersion, and the temperature is lowered to 40-60° C. after complete dissolution, and 6-1 0 parts by weight of the vinyl acetate monomer and 1-2 parts by weight of the initiator solution, heating to 70-80° C. for 20-40 minutes of polymerization reaction to obtain a seed emulsion; the mixed monomer and 3-5 parts by weight of the initiator solution are respectively and simultaneously added dropwise to the seed emulsion for 3-4 hours, and after the addition is completed, the temperature is raised to 70-80° C., the polymerization reaction is carried out for 50-80 minutes, and then cooled to 30-40° C., and the material is filtered to obtain the polyvinyl acetate emulsion woodworking adhesive.
Citation Information
Patent Citations
Long-open-time woodworking adhesive based on maltose syrup modified polyvinyl acetate emulsion
CN109355039A